1994
DOI: 10.1002/j.1460-2075.1994.tb06541.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cytochrome oxidase, an enzyme older than atmospheric oxygen.

Abstract: Cytochrome oxidase is a key enzyme in aerobic metabolism. All the recorded eubacterial (domain Bacteria) and archaebacterial (Archaea) sequences of subunits 1 and 2 of this protein complex have been used for a comprehensive evolutionary analysis. The phylogenetic trees reveal several processes of gene duplication. Some of these are ancient, having occurred in the common ancestor of Bacteria and Archaea, whereas others have occurred in specific lines of Bacteria. We show that eubacterial quinol oxidase was deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(202 citation statements)
references
References 75 publications
13
188
1
Order By: Relevance
“…The position of branches of both types of haem-copper oxidase of Pyrobaculum is consistent with the proposed idea that the SoxB-type branch and the SoxM-type branch of haem-copper oxidases evolved from an early gene duplication preceding the divergence of archaea and bacteria (Fig. 7) (Castresana et al, 1994). The phylogenetic analysis of cytochrome b showed that thermophilic archaea are clearly divided from the bacterial branch.…”
Section: Evolutionary Aspectssupporting
confidence: 87%
See 2 more Smart Citations
“…The position of branches of both types of haem-copper oxidase of Pyrobaculum is consistent with the proposed idea that the SoxB-type branch and the SoxM-type branch of haem-copper oxidases evolved from an early gene duplication preceding the divergence of archaea and bacteria (Fig. 7) (Castresana et al, 1994). The phylogenetic analysis of cytochrome b showed that thermophilic archaea are clearly divided from the bacterial branch.…”
Section: Evolutionary Aspectssupporting
confidence: 87%
“…Most terminal oxidases belong to the haem-copper oxidase family; a few of them belong to the cyanide-insensitive alternative oxidase group (Garcia-Horsman et al, 1994). Phylogenetic and biochemical analysis of haem-copper oxidases indicates that the haem-copper oxidase family can be divided into three groups: FixN-, SoxB-and SoxM-type (Castresana et al, 1994;Garcia-Horsman et al, 1994). Mitochondria have one SoxM-type terminal oxidase but a number of bacteria and archaea have multiple terminal oxidases and the regulation of multiple oxidases is the important factor in their adaptation to changes in oxygen tension in their habitat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of these geological arguments, the history of oxidase enzymes places other constraints on the origins of aerobiosis (30,43,44). Although there is active debate on the phylogenetic history of oxidase enzymes, recent models (30,43,44) support an ancient origin, even before the evolution of oxygen-producing cyanobacteria (45). Without a cyanobacterial source, oxygen could have come from abiotic sources, such as the rainout and disproportionation (by catalase enzymes) of atmospherically produced H 2 O 2 at the Earth's surface.…”
Section: Resultsmentioning
confidence: 99%
“…Recent taxonomic study on COXs and NORs showed the congruence of A-type COX and 16S rRNA tree at the Archaea/Bacteria domain and suggested the presence of A-type COX in common ancestor (22). On the other hand, based on the assumption that NO was present in the atmosphere prior to O 2 , Castresana et al (23) suggested that NORs were the first respiratory enzymes to appear, and C-type COXs was evolved from NORs. Our structural data on NORs cannot clarify the order of the appearance of the respiratory enzymes.…”
Section: Structures Of Bacterial Nors: Structural Evidence For Evolutmentioning
confidence: 99%